MORPHOLOGICAL TYPES OF 254 RICH PF GALAXY CLUSTERS - Panko, E. A.; Andrievsky, S. M.; Gotsulyak, A. V. (Одеські астрономічні публікації, 2014)
We determined the morphological types for 254 rich galaxy clusters from the PF Catalogue of Galaxy Clusters and Groups. The data set contains the PF galaxy clusters, which have no ACO coinciding ones. The applied morphological scheme was combined of the prevalent classifications, such as Bautz-Morgan, Rood-Sastry etc approaches. We assigned the morphological types using numerical criteria and taking into consideration concentration tothe cluster center, the signs of preferential direction or plane in the cluster, and the positions of the brightest galaxies. The features of the data set are discussed.